Hippocampal Brain Derived Neurothropic Factor Levels in Response to Anaerobic Physical Exercises - Mohammad Zulkarnain; Rostika Flora; Juliastuti Juliastuti; Anita Apriany; Dewi Pujiana; Septi Andrianti (Intelektual Pustaka Media Utama, 2017)
Anaerobic physical exercise does not only improve body fitness, but it also increases cognitive functions. The increase of cognitive functions is mediated by the increase of Brain Derived Neurothropic Factor (BDNF) level. Several studies revealed that anaerobic physical exercise can increase the BDNF level inhippocampal tissues. However, it is still questionable whether or notthe frequency of exercise influences the production of BDNF inhippocampal tissues. This study was to find out the BDNF mean level inhippocampal tissue of Wistarrats which were treated with anaerobic physical exercises conducted in different frequencies.This study used post test only control groupdesign. The research subject was 28 rats of Rattusnorvegicus strain wistar divided into 4 groups; 1 control group and 3 treatment groups (one-time, three-time, and five times a week treatment). The anaerobic physical exercise used animal treadmill running in the speed of 35m/min for 20 minutes at four-minute intervals. The mean levels of BDNF were increased in all treatment groups compared with control group (151.588 vs 57.059). The highest mean level of hippocampal tissue BDNF was found in the treatment group of three times a week (177.701). There was a significant difference in BDNF mean levels of Wistar rat brain tissues among the treatment groups.